A Comparative Study on Drought Stress Response In Vitro and In Vivo Propagated Fragaria vesca Plants - Marta Rokosa; Małgorzata Mikiciuk; Danuta Kulpa; Piotr Ptak (Agriculture)
The evaluation of plant responses to water deficit in the substrate, particularly in the context of intensifying climate change, represents a critical factor for ensuring stable agricultural production, economic resilience, and food security. The primary objective of this study was to compare the physiological and biochemical responses to water deficit in conventional cultivation of Fragaria vesca plants propagated both in vitro and in vivo. The research encompassed measurements of gas exchange parameters, chlorophyll “a” fluorescence, photosynthetic pigment and proline content in leaves, leaf relative water content index, total fruit yield, single fruit weight, fresh and dry mass of the root system, as well as the concentrations of K, Ca, Mg, Na, Cu, Zn, Mn, and Mo. Additionally, the ratio of monovalent to divalent cations in leaves, roots, and crowns was analyzed. The results revealed significant differences between the experimental variants under optimal conditions and their respective responses to drought stress. Plants derived from in vitro cultures, despite exhibiting initially lower physiological trait values, demonstrated higher yield potential (no significant difference in the yield of fresh fruit mass compared to a 78% reduction). However, a long-term lack of water caused greater damage to their photosynthetic system—a reduction in physiological traits to 80% was observed, compared to a maximum decrease of 40% in plants derived from seedlings. The results highlight that environmental conditions and the acclimatization process of plants derived from in vitro cultures can significantly influence their adaptive potential and productivity.